Proliferation Marker Ki67 as a Stratification Index of Adjuvant Chemotherapy for Resectable Mucosal Melanoma - Tang, Lirui; Wei, Xiaoting; Li, Caili; Dai, Jie; Bai, Xue; Mao, Lili; Chi, Zhihong; Cui, Chuanliang; Lian, Bin; Tang, Bixia; Du, Yu; Wang, Xuan; et al. (Frontiers in Oncology, 2022)
Background: Adjuvant chemotherapy has been shown to produce a favorable prognosis for patients with resectable mucosal melanoma (MM), resulting in the need for stratification to optimally select patients to benefit from adjuvant therapy. This study analyzed Ki67 as a potential stratification index for adjuvant chemotherapy in resectable MM. Methods: Patients with resected MM who received subsequent adjuvant therapy in Beijing Cancer Hospital between 2010 and 2018 were retrospectively enrolled and analyzed. Relapse-free survival (RFS) and melanoma-specific survival (MSS) curves were used to perform the survival comparisons across different subgroups. Results: From Jan 2010 to Dec 2018, 1106 MM patients were screened from a database of 4706 patients and 175 of these patients were finally enrolled. A total of 100 patients received temozolomide (TMZ)-based adjuvant chemotherapy and 75 patients received high-dose interferon-α2b (HDI) adjuvant therapy. Compared with HDI, patients who received TMZ-based adjuvant chemotherapy had significantly superior RFS (21.0 vs. 9.6 months, P = 0.002). For patients with low Ki67 expression (<30%), the two regimens showed no significant difference for impact on RFS (33.9 vs. 22.7 months, P = 0.329). However, for patients with high Ki67 expression (≥30%), TMZ-based adjuvant chemotherapy achieved favorable RFS compared with HDI (18.0 vs. 6.7 months, P < 0.001) and tended to improve MSS compared to HDI (41.4 vs. 25.1 months, P = 0.067). Conclusion: Compared with HDI, adjuvant chemotherapy may be more relevant for patients with Ki67 ≥ 30%. Ki67 may serve as a potential index to distinguish populations benefiting from adjuvant chemotherapy in resectable MM, and may provide a basis for stratification in the selection of adjuvant regimens.